PENINGKATKAN KEMAMPUAN PENGELOLAAN KEUANGAN KELUARGA MELALUI PENDIDIKAN MELEK KEUANGAN SUAMI ISTRI - Galuh Aditya; Wakhdan Wakhdan (FE Program Studi Manajemen, 2020)
This study aims to illustrate clearly the extent to which financial literacy education followed by a married couple of Credit Union members Angudi Laras can improve the ability to manage family finances.This research is qualitative in nature through transcribing the results of interviews, reducing data, analyzing, interpreting data and triangulation. The results showed that husband and wife who had attended financial literacy education organized by the Angudi Laras Credit Union had a role in increasing understanding of family needs for savings or investment, husband and wife increased understanding in basic financial concepts, an increase in financial discussions and problems between husband and wife , become better at making choices in managing finances and debt, and increase competence in responding to changes that can affect finance.Keywords: capacity building, financial management, financial literacy education.